First Nations child poverty a literature review and analysis - Brittain, Melisa; Blackstock, Cindy; First Nations Child and Family Caring Society (Ottawa, Ont. : First Nations Children's Action Research and Education Service, 2015)
This is a literature review and analysis of existing research on First Nations child poverty, examining its historical and contemporary causes and effects. The authors also evaluate existing poverty measures and outline existing and proposed interventions to address the continued and deliberate impoverishment of First Nations children.
Keywords: Child welfare -- Canada; Children -- Economic conditions -- Canada